2009
DOI: 10.1111/j.1468-0491.2009.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

New Governance, the Internet, and Country Code Top‐Level Domains in Europe

Abstract: Much academic work on governance in recent years has explored responses which states have made to sectors of the economy, usually historically well-rooted nationally, which have been subject to globalizing pressures. Less work exists on responses which are being made to new parts of the economy emerging outside the nation state with inherently global characteristics. The Internet -and specifically its naming and addressing system -provides an example of how the state has aimed to assert public interest governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Several studies have analyzed how far digital administration has developed (e.g. West, 2000West, , 2001West, , 2002West, , 2003West, , 2004Caba et al, 2005;Torres et al, 2005Torres et al, , 2006Christou and Simpson, 2009), while others havefocused on format and volume, the quality of the budgetary and financial information disclosed (e.g. Laswad et al, 2005;Cárcaba and García, 2008) and factors associated with the degree of development of e-government (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed how far digital administration has developed (e.g. West, 2000West, , 2001West, , 2002West, , 2003West, , 2004Caba et al, 2005;Torres et al, 2005Torres et al, , 2006Christou and Simpson, 2009), while others havefocused on format and volume, the quality of the budgetary and financial information disclosed (e.g. Laswad et al, 2005;Cárcaba and García, 2008) and factors associated with the degree of development of e-government (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Extant research on the evolution of e-government (West, 2004;Caba et al, 2005;Torres et al, 2006;Christou and Simpson, 2009) focus on the numerous factors that influence the growth of e-government in the past decade and found that income levels, strength of institutions and the commitment of the government to promoting e-government were the most important factors. Other studies focus on the factors that determine the level of development of e-government (Kim, 2007;Siau and Long, 2006) and suggest that one of the most important factors was the economic growth of the country.…”
Section: Ict Enabled E-governmentmentioning
confidence: 99%
“…Moreover, some of the owners refuse to use .tr as a way of opposing the particular national requirements embedded in the ccTLD. Compared to the application process for .tr, the one for .pl is less controlled by the state and much simpler bureaucratically, which influences the greater popularity of .pl in general (Christou and Simpson, 2009; for recent statistics see CENTR, 2014). Additionally, no ideological requirements regarding respectability are specified for obtaining .pl, which makes the ccTLD a vaguer, and thus more open, marker of nationality online.…”
Section: Mediation Of Nationhood On Lgbtq Websitesmentioning
confidence: 99%